1992
DOI: 10.1161/01.atv.12.7.830
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary olive and sunflower oils on the lipid composition of the aorta and platelets and on blood eicosanoids in rats.

Abstract: The effects on aortic and platelet fatty acid compositions and on blood levels of prostacyclin and thromboxane A2 of low- and high-fat diets containing olive oil or sunflower oil were studied. For 4 weeks, four groups of weanling rats were fed a basal diet containing 5% or 25% olive oil or sunflower oil. Rats fed olive oil diets showed higher levels of 18:1(n-9) and polyunsaturated fatty acids of the n-3 series and lower percentages of 18:0 and 18:2(n-6) in aortic and platelet phosphatidylcholine and phosphati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 32 publications
2
21
0
Order By: Relevance
“…It is known that the degree of unsaturation of dietary oil influences the fatty acid composition of cells, fundamentally in the phospholipids of the cell membrane (Ruiz-Gutiérrez et al 1990, and OO feeding leads to changes in lipid metabolism of the vascular compartment that could be favourable in the prevention of thrombosis and atherosclerosis (Navarro et al 1992). We wanted to verify that the same changes occurred with regard to endothelial function.…”
Section: Discussionmentioning
confidence: 98%
“…It is known that the degree of unsaturation of dietary oil influences the fatty acid composition of cells, fundamentally in the phospholipids of the cell membrane (Ruiz-Gutiérrez et al 1990, and OO feeding leads to changes in lipid metabolism of the vascular compartment that could be favourable in the prevention of thrombosis and atherosclerosis (Navarro et al 1992). We wanted to verify that the same changes occurred with regard to endothelial function.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies showed that a diet rich in saturated FA may lead to changes in the oxidative damage in different brain areas, which are basically observed by increased LP together with decreased antioxidant defenses, whereas dietary olive oil could reverse those parameters [56], as observed here. Some reports showed that n-3-or n-6-enriched diet results in less production of lipid peroxides in both brain and liver [57,58]. In fact, it is suggested that the effect of n-6 FA may result from higher antioxidant defenses in the brain [59].…”
Section: Discussionmentioning
confidence: 99%
“…These results appear to be a consequence of the equilibrium between pro-and anti-oxidant factors. Thus, (i) dietary intervention decreases the PUFA content of lipoproteins, making them less susceptible to peroxidation [19,44]; (ii) MUFA n-6 increase the PUFA n-3 content of platelet and membrane phospholipids more than PUFA n-6 [45], which in turn increases susceptibility of lipoprotein peroxidation during the EVOO diet; (iii) Phenolic compounds and squalene were higher in the EVOO diet while tocopherols and some sterols were higher in the SO diet. Thus, their respective antioxidant properties would be counterbalanced [4,19].…”
Section: Oil Exchange and Lipoproteinsmentioning
confidence: 99%